2022
DOI: 10.1108/ijchm-10-2021-1322
|View full text |Cite
|
Sign up to set email alerts
|

Biophilic design for urban hotels – prospective hospitality employees’ perspectives

Abstract: Purpose The purpose of this paper is to investigate a holistic way of incorporating biophilic building design that creates a restorative environment attractive to prospective urban hotel employees. This study additionally examines the role of perceived well-being from nature attributes and associated impacts on emotions and likelihood to choose to work for a hotel with nature attributes. Design/methodology/approach This study used a conjoint analysis to detect the most resotrative individual and combinations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
(92 reference statements)
1
9
0
Order By: Relevance
“…To achieve this purpose, a three‐condition (biophilic design: nonbiophilic vs. weak vs. strong; coded as 0, 1, and 2 respectively) between‐subjects experimental study was executed in the existing restaurant environment. In terms of developing biophilic design stimuli, this study accepted the previous literature's criticism that manipulation of one biophilic attribute (e.g., wooden wall) is not a realistic reflection on current management practices (Guzzo et al, 2022), thus, developing the overall biophilic ambience was an important step in developing stimuli. To this end, the degree of the biophilic design was manipulated by altering the levels of indoor landscaping (e.g., floor‐to‐ceiling windows), greenery, and interior design materials (e.g., clay vase, wooden wall).…”
Section: Studysupporting
confidence: 54%
See 3 more Smart Citations
“…To achieve this purpose, a three‐condition (biophilic design: nonbiophilic vs. weak vs. strong; coded as 0, 1, and 2 respectively) between‐subjects experimental study was executed in the existing restaurant environment. In terms of developing biophilic design stimuli, this study accepted the previous literature's criticism that manipulation of one biophilic attribute (e.g., wooden wall) is not a realistic reflection on current management practices (Guzzo et al, 2022), thus, developing the overall biophilic ambience was an important step in developing stimuli. To this end, the degree of the biophilic design was manipulated by altering the levels of indoor landscaping (e.g., floor‐to‐ceiling windows), greenery, and interior design materials (e.g., clay vase, wooden wall).…”
Section: Studysupporting
confidence: 54%
“…In biophilic design literature, psychoevolutionary theory suggests the possibility of green attributes' adverse effects; that is, green attributes like trees and grass can trigger protection mechanisms, as people can detect danger from nature (e.g., insects, mold, etc.) as well as beneficial outcomes (Guzzo et al, 2022). Similarly, the sensory literature has found that excessive exposure to sensory stimuli can elicit negative responses, resulting in an inverted U‐shaped relationship between sensory stimuli and consumers' reactions (Jang et al, 2018).…”
Section: Studymentioning
confidence: 99%
See 2 more Smart Citations
“…In the next paper titled “Biophilic design for urban hotels – Prospective hospitality employees’ perspectives,” Guzzo et al (2022) investigated the best and most holistic way of facilitating biophilic building design for prospective urban hotel employees. The study also examined the role of perceived well-being from nature attributes and how it influences employee emotions and willingness to work for a hotel with nature attributes.…”
Section: The Papers In This Special Issuementioning
confidence: 99%